Korozijska obstojnost jeklene litine s povečano vsebnostjo Si - Godec, Boštjan (Kovine zlitine tehnologije, 1995)
High alloyed Si-bearing cast steels with low content of carbon were produced. The electrochemical corrosion tests were performed to find the influence of silicon on corrosion resistivity of cast steels in high oxidizing media and its role of the passive layer formation.
Keywords: korozija; silicij; jeklena litina